2012
DOI: 10.1080/14786435.2011.634850
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary grooving in bi-crystal thin films induced by surface drift-diffusion driven by capillary forces and applied uniaxial tensile stresses

Abstract: Grain boundary (GB) grooving, induced by surface drift-diffusion and driven by the combined actions of capillary forces and applied uniaxial tensile stresses, is investigated in bi-crystal thin films using self-consistent dynamical computer simulations. A physico-mathematical model, based on the irreversible thermodynamics treatment of surfaces and interfaces with singularities allowed auto-control of the otherwise free-motion of the triple junction at the intersection of the grooving surface and the GB, witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…33,34 The gradual deepening of the grain-boundary groove by the combination of surface diffusion (on a short time scale) and grain-boundary diffusion (on a larger time scale) is likely influenced by the intrinsic stress state of the film and the surface-shape of the grains. 34,35 It can thus be concluded that an advanced model description of the kinetics of the tensile film-force rise during growth interruptions should incorporate dependencies of the compressive stress relaxation rate on the pre-interruption deposition rate and the average grain size, as resulting from different rates of grain-boundary grooving at the film surface upon growth interruption.…”
Section: B Proposed Mechanism Dmentioning
confidence: 99%
“…33,34 The gradual deepening of the grain-boundary groove by the combination of surface diffusion (on a short time scale) and grain-boundary diffusion (on a larger time scale) is likely influenced by the intrinsic stress state of the film and the surface-shape of the grains. 34,35 It can thus be concluded that an advanced model description of the kinetics of the tensile film-force rise during growth interruptions should incorporate dependencies of the compressive stress relaxation rate on the pre-interruption deposition rate and the average grain size, as resulting from different rates of grain-boundary grooving at the film surface upon growth interruption.…”
Section: B Proposed Mechanism Dmentioning
confidence: 99%
“…The crucial role of elastic dipole tensor interactions (EDTI) on driving force for surface diffusion was considered previously, under tensile [15] and compressive [16] uniaxial stresses applied to freestanding thin films. As the dimensions of ultrathin films approached, small thicknesses can lead to great stress gradients, which act as a driving force for grain boundary diffusion [17].…”
Section: Introductionmentioning
confidence: 99%
“…Later, other authors also employed the concept for bulk [19] and grain boundary [20] diffusion. According to our best knowledge, excluding our recent work on the effects of applied uniaxial tension stresses on GB grooving [21], there exists neither gross scale simulation nor analytical work that reflects the dominant effect of long range surface drift-diffusion driven by the stress gradient in the literature. The main reason for this is that the surface is always assumed to be traction free, and thus the Herring's force vanishes identically (see Appendix).…”
Section: Introductionmentioning
confidence: 99%